Blood Brain Barrier Permeability Could Be a Biomarker to Predict Severity of Neuromyelitis Optica Spectrum Disorders: A Retrospective Analysis - Wang, Ying; Zhu, Mingqin; Liu, Caiyun; Han, Jinming; Lang, Wenjuan; Gao, Yang; Lu, Chao; Wang, Shuang; Hou, Shuai; Zheng, Nannan; Wang, Dong; Chen, Yang; et al. (Frontiers in Neurology, 2018)
Background: Blood-brain barrier (BBB) pathology exists in neuromyelitis optica spectrum disorders (NMOSD). However, the clinical use of BBB permeability, such as predicting disease severity of NMOSD, has rarely been studied in a large cohort of patients. Objectives: The current study explored the association between BBB permeability and clinical parameters in order to assess if BBB permeability could be a biomarker to predict disease severity and clinical characteristics of NMOSD. Methods: Among 69 enrolled NMOSD patients, 47 with albumin index over 5 X 10-3 were assigned to the increased BBB permeability group, and the remaining 22 were to the normal BBB permeability group. Disease severity was assessed using the Expanded Disability Status Scale (EDSS). Results: Patients in the increased BBB permeability group had significantly higher EDSS scores, anti-aquporin-4 immunoglobulin G titers, more dense cerebrospinal fluid protein concentrations, white blood cell counts, myelin basic protein levels and more dense complement 3 concentrations than found in the comparative normal BBB permeability group. The albumin index was positively correlated to the length of lesions in spinal cord. Conclusions: BBB permeability was associated with clinical features, laboratory results and radiological data of NMOSD patients, and may be a potential biomarker to predict disease severity and clinical characteristics of NMOSD.